Transanal mesorectal excision: early outcomes in Australia and New Zealand. Issue 2 (9th January 2021) - Lau, S; Kong, J; Bell, S; Heriot, A; Stevenson, A; Moloney, J; Hayes, J; Merrie, A; Eglinton, T; Guest, G; Clark, D; Warrier, S
Abstract: Background: Transanal total mesorectal excision (taTME) aims to overcome some of the technical challenges faced when operating on mid and low rectal cancers. Specimen quality has been confirmed previously, but recent concerns have been raised about oncological safety. This multicentre prospective study aimed to evaluate the safety of taTME among early adopters in Australia and New Zealand. Methods: Data from all consecutive patients who had taTME for rectal cancer from July 2014 to February 2020 at six tertiary referral centres in Australasia were recorded and analysed. Results: A total of 308 patients of median age of 64 years underwent taTME. Some 75.6 per cent of patients were men, and the median BMI was 26.8 kg/m 2 . The median distance of tumour from anal verge was 7 cm. Neoadjuvant chemoradiotherapy was administered to 57.8 per cent of patients. The anastomotic leak rate was 8.1 per cent and there was no mortality within 30 days of surgery. Pathological examination found a complete mesorectum in 295 patients (95.8 per cent), a near-complete mesorectum in seven patients (2.3 per cent), and an incomplete mesorectum in six patients (1.9 per cent). The circumferential resection margin and distal resection margin was involved in nine patients (2.9 per cent), and two patients (0.6 per cent) respectively. Over a median follow-up of 22 months, the local recurrence rate was 1.9 per cent and median time to local recurrence was 30.5 months. Conclusion: This study showed that, with appropriate training and supervision, skilled minimally invasive rectal cancer surgeons can perform taTME with similar pathological and oncological results to open and laparoscopic surgery. Abstract : Transanal total mesorectal excision (taTME) was designed to overcome challenges faced when operating on mid and low rectal cancers. Although studies have shown a good quality specimen with this technique, taTME is currently at a crossroad primarily due to concerns regarding its oncological safety. This multicentre, prospective study aims to evaluate the safety of taTME among early adopters in Australia and New Zealand. Equivalent to open and laparoscopic